Examining the readability of accounting narratives derived from earnings management - Gutiérrez-Ponce, Herenia; Chamizo González, Julian; Al-Mohareb, Manar (Journal of Business Economics and Management, 2023)
This study investigates whether language difference affects the readability scores of accounting narratives derived from earnings management practices in 226 companies in the UK, Spain, and Jordan from 2017 to 2021.Our analytical method applies three of the most significant readability measures based on the characteristics of each language, as well as multiple linear and logistic regression models, to demonstrate the impact of language differences on the readability of accounting narratives. The findings indicate that earnings management practices significantly affect the readability of accounting disclosures/narratives, and that past financial profitability moderates this relationship. The implications of the findings reported will help decision-makers better understand the quality and readability of accounting narratives derived from companies’ earnings management. Our analysis also has implications for how stakeholders, accounting policymakers, financial statement auditors, and academics understand the relationship between accounting reporting narratives and earnings management. First published online 17 January 2024